Association between previous abortion history and risk of autism spectrum disorders among offspring: a meta-analysis - Ensiyeh Jenabi; Erfan Ayubi; Saeid Bashirian; Mahdieh Seyedi; Mohammad Rezaei (The Korean Pediatric Society, 2023)
Background Previous studies have been showed an association between previous abortion history and risk of Autism spectrum disorders (ASD). However, there is still controversy about true effect estimate of the association. Purpose This meta-analysis aimed to evaluate the association between previous abortion history and the risk of ASD. Methods A systematic search was performed using PubMed, Scopus, and Web of Sciences databases to identify potential studies published until December 2021. The presence of statistical heterogeneity was determined using the I2 value. In the case of substantial heterogeneity, the random-effects model meta-analysis was used to estimate the pooled relative risks. The publication bias was assessed using the Egger and Begg tests. Results Thirteen studies with a total of 331,779 children remained in the present meta-analysis. The estimated odds ratio of the risk of ASD associated with previous abortion history was 1.64 (95% confidence interval [CI], 1.28-2.0; I2=61.7%) in adjusted studies and 1.10 (95% CI, 1.01-1.20; I2=0.0%) in crude studies, based on the random effect model. There was moderate heterogeneity in adjusted studies. The p values for Egger and Begg regression among children with ASD were 0.393 and 0.056, respectively. Conclusion This meta-analysis suggests that children born from mothers with a history of previous abortion have an increased risk of development of ASD compared to children of mothers without a history of previous abortion.